Wildlife Disease and Health in Conservation - Radcliffe, Robin W.; Jessup, David A. (Book collections on Project MUSE., 2023)
"This title explores the origins, impacts and responses to diseases that are particularly damaging, persistent and/or are currently threatening wildlife conservation"--